HUBUNGAN MATRIKS AB DAN BA PADA STRUKTUR JORDAN NILPOTEN - Sondang Purnamasari Pakpahan; Elvina Herawaty (Jurnal Matematika Sains dan Teknologi, 2009)
In this paper, we give another proof about the relationship between AB and BA with eigenvalue zero that reduced by structure Jordan for nilpoten matrix